Liberalization, Crisis, Intervention : The Chilean Financial System, 1975-1985. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper surveys the evolution of the Chilean financial system from 1975 to 1985, analyzes the causes and the consequences of the major crisis in the financial system during 1981-83, and examines the measures adapted to contain the crisis and restore the financial system to normalcy. The analysis suggests that certain features of the financial sector--growing loans of dubious quality, limited central bank supervision--raised the vulnerability of the sector to the external shocks and macroeconomic policy changes experienced by Chile. Channels through which financial sector troubles may have exacerbated the impact of real shocks are also explored.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet